Multibody simulation of carved turns in alpine skiing - Nachbauer, W.; Heinrich D.; Kaps, P.; Mössner, M.; Schretter, H. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume I: Computer Science in Sports., 2008)
Carved turns with Alpine Skis were investigated using a Computer Simulation model. Varied input data to the model were snow conditions, edging of the skis, and the velocity of the skier. Results include the pressure distribution along the running surface of the skis and the trajectory of the skier.